Impact of Different Plant Canopy Traits on Sorghum Yields - M. F. Lucero; A. J. P. Carcedo; L. Marziotte; L. Mayor; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2023)
Studying changes in plant canopy can help to improve plant architecture and increase yields. Specifically, for sorghum (Sorghum bicolorL.), characterizing and identifying relevant canopy traits can be helpful not only to improve its productivity but to better fit this crop in the rotation from a system perspective. With this purpose, morphological characteristics of 20 sorghum hybrids were measured during the 2022 growing season in Wamego, KS, U.S. (United States). The most relevant canopy traits examined were leaf angle and leaf area at leaf- and at canopy-level (leaf area index, LAI), all determined at different points of the crop growth cycle (seventh-leaf, V7, flowering, and physiological maturity). Furthermore, duration of the vegetative and reproductive phases were also recorded as days to flowering, and days to maturity. A conditional decision tree analysis was employed to cluster the hybrids according to their variation in canopy characteristics and impact on yield. In summary, end of season LAI (at physiological maturity) was one of the most relevant plant canopy traits to group the hybrids and it accounted for 70% of the variation. Hybrids with high LAI at V7 and low LAI at maturity, in addition to their longer time to maturity, presented greater yields. These findings can lead to future investigation using the same traits under different climatic conditions.
Keywords: Sorghum bicolor L. Moench; hybrids; canopy architecture; phenology; leaf area index